Religion, spirituality, and susceptibility to conspiracy theories: examining the role of analytic thinking and post-critical beliefs - Jedinger, Alexander (Politics and religion, 2024)
The COVID-19 pandemic has increased the political and scholarly attention on conspiracy theories. Among other predictors, religious and spiritual influences on conspiracy beliefs have been widely discussed in the literature. We suggest analyzing the relationship between religion and spirituality on the one hand and conspiracy beliefs on the other hand from the perspective of religious information processing. Based on the Post-Critical Beliefs Scale (PCBS), we argue that literal interpretations of religious information are positively associated with conspiracy beliefs. Furthermore, we assume that individual differences in analytic cognitive style account for the relationship between religious attitudes, spirituality, and conspiracism. Using a quota sample of German adults, we find that literal interpretations of religious content positively correlate with conspiracy beliefs for the literal affirmation of transcendence (e.g., orthodoxy) and the literal disaffirmation of transcendence (e.g., atheism). These findings suggest that religious information processing is related to conspiracy beliefs for religious and nonreligious individuals. Moreover, our results show a stable association between holistic spirituality and conspiracy beliefs. The relationships between different types of religious attitudes, spirituality, and conspiracy beliefs hold, even after accounting for analytic (versus intuitive) thinking. The implications for the study of religious attitudes and conspiracy beliefs are discussed.